East Asia and Pacific Update, December 2008 : East Asia - Navigating the Perfect Storm - World Bank (World Bank, Washington, DC, 2020)
As the global economy finds itself in the worst financial crisis since the great depression, the East Asia and Pacific region has not been spared the full fury of the economic storm. The surge and subsequent drop in food and fuel prices was followed by the intensification in the financial crisis that began in mid- 2007 in the U.S., deepened through the first half of 2008, and took a sharp turn for the worse after September 15. Even as East Asian policymakers were battling the previous crisis in late 2007 and early 2008 - the rise in inflation following the steep increases in food and fuel prices they were confronted by sudden falls in equity prices and exchange rates, sharp increases in short-term interest rates, and an abrupt deceleration in export growth. The epicenter of the storm was in the developed countries, but its reach spread quickly across the globe. The failure of important financial institutions in the major financial systems froze interbank and credit markets around the world and revised the price of risk upward, triggering a global liquidity shortage. The ensuing search for liquidity worldwide prompted, among other things, the sale of equity and debt securities and the withdrawal of capital from emerging markets, destabilizing banking systems far from the center of the crisis. Boosts to liquidity and injections of capital in financial institutions by developed country authorities may avert a systemic meltdown of financial markets, but heightened risk aversion and an ongoing deleveraging across the world is causing capital to retreat from developing countries and the cost of financing to rise. The loss of trust, breakdown in financial markets, and curtailment of bank loans have hit investment, production, and trade, causing global growth to slow rapidly. Japan and Europe are already in recession, and the US is expected to follow soon. All three are expected to contract further in 2009, dampening import demand and resulting in the first decline in world trade volumes in a quarter century.